Linguistic analysis on the construction of satire in Nigerian political cartoons : The example of newspaper cartoons. - Sani, Iro; Abdullah, Mardziah Hayati; Mohamad Ali, Afida; Abdullah, Faiz Sathi (Academic Journals, 2012)
Political cartoons constitute a form of media text whose verbal and visual elements have made them aninteresting research field across academic disciplines. The 21st century has witnessed a considerableresearch on political cartoons. This increasing research interest indicates that political cartoons havesuccessfully constituted a distinct multimodal genre within media discourses. Political cartoons areused to express opinions, construct valuable arguments and provide specific knowledge oncontemporary social issues. However, the analysis of the cartoons from linguistic perspectives remainsunder-researched. This paper aims at contributing to the knowledge of political cartoon research byanalyzing the linguistic elements used in the cartoon written texts to illustrate how Nigerian cartoonistsspecifically use language to construct satire as a means that could be used perhaps to initiatingpositive social and political reforms in Nigeria. The method of analysis used in this paper as itsframework of analysis, comprises of perceptual theory of satire and linguistic analytical frameworkwithin the realm of critical discourse analysis. Semiotic discussion on semiotic modes of the cartoonshas also been incorporated in the analysis. From the findings of the study, a distinct lexical topology foridentifying lexical items and their distribution in the cartoon written texts has been developed. Thetopology comprises of five items as follows: loan word, coinage, word class, denotation andconnotation. Additionally, Nigerian cartoonists use interjections frequently in the cartoon written textsto create satirical impressions about political leaders, because interjections are used to express astrong emotions or feelings. Given the linguistic and nonlinguistic elements contained in the cartoontexts, cartoons could be harnessed to provide additional insights on how language is specifically usedin media discourse